Recruitment of Host Nuclear Pore Components to the Vicinity of Theileria Schizonts - Sandra Huber (American Society for Microbiology, 2020)
ABSTRACT Parasitic protozoans of the genus Theileria are intracellular pathogens that induce the cellular transformation of leukocytes, causing uncontrolled proliferation of the infected host cell. The transforming stage of the parasite has a strictly intracellular lifestyle and ensures its distribution to both daughter cells during host cell cytokinesis by aligning itself across the metaphase plate and by binding tightly to central spindle and astral microtubules. Given the importance of the parasite surface in maintaining interactions with host microtubules, we analyzed the ultrastructure of the host-parasite interface using transmission electron microscopy combined with high-resolution fluorescence microscopy and live-cell imaging. We show that porous membranes, termed annulate lamellae (AL), closely associate with the Theileria surface in infected T cells, B cells, and macrophages and are not detectable in noninfected bovine cell lines such as BL20 or BoMACs. AL are membranous structures found in the cytoplasm of fast-proliferating cells such as cancer cells, oocytes, and embryonic cells. Although AL were first observed more than 60 years ago, the function of these organelles is still not known. Indirect immunofluorescence analysis with a pan-nuclear pore complex antibody, combined with overexpression of a panel of nuclear pore proteins, revealed that the parasite recruits nuclear pore complex components close to its surface. Importantly, we show that, in addition to structural components of the nuclear pore complex, nuclear trafficking machinery, including importin beta 1, RanGAP1, and the small GTPase Ran, also accumulated close to the parasite surface. IMPORTANCE Theileria schizonts are the only known eukaryotic organisms capable of transforming another eukaryotic cell; as such, probing of the interactions that occur at the host-parasite interface is likely to lead to novel insights into the cell biology underlying leukocyte proliferation and transformation. Little is known about how the parasite communicates with its host or by what route secreted parasite proteins are translocated into the host, and we propose that nuclear trafficking machinery at the parasite surface might play a role in this. The function of AL remains completely unknown, and our work provides a basis for further investigation into the contribution that these porous, cytomembranous structures might make to the survival of fast-growing transformed cells.